A Standardized, Bundled Approach to Providing Geriatric‐Focused Acute Care. Issue 5 (18th April 2014) - Mattison, Melissa L. P.; Catic, Angela; Davis, Roger B.; Olveczky, Daniele; Moran, Julie; Yang, Julius; Aronson, Mark; Zeidel, Mark; Lipsitz, Lewis; Marcantonio, Edward R.
<x xml:space="preserve">Abstract</x> Objectives To determine whether a bundled intervention can increase detection of delirium and facilitate safer use of high‐risk medications. Design Pre‐post interventional trial. Setting Large academic medical center. Participants Individuals aged 70 and older (n = 19, 949) admitted between May 1, 2008, September 30, 2011. Individuals aged 80 and older admitted after April 26, 2010, received the intervention, those aged 80 and older admitted before were primary controls, and those aged 70 to 79 were concurrent controls. Intervention The intervention uses a checklist promoting delirium prevention, recognition and management, and modifies the computerized provider order entry system to provide care focused on elderly adults. Measurements Frequency of orders for activating the rapid response team for altered mental status, frequency of orders for haloperidol in excess of 0.5 mg or intravenous (IV) morphine in excess of 2 mg, and discharge disposition. Results Participants receiving the intervention had a mean age of 86.1 ± 4.6; 58.2% were female. The number of orders to activate the rapid response team for altered mental status increased in participants receiving the bundle and in controls (odds ratio (OR) for the difference of differences = 1.23 (95% confidence interval (CI) = 0.68–2.24, P = .49)). Participants receiving the bundle were less likely to receive more than 0.5 mg of IV, intramuscular, or oral haloperidol (OR = 0.60, 95% CI = 0.39–0.91, P = .02) and more than 2 mg of IV morphine (OR = 0.52, 95% CI = 0.42–0.63, P < .001). Participants who received the bundle were more likely to be discharged home than to extended care facilities (OR = 1.18, 95% CI = 1.04–1.35, P = .01). Conclusion An intervention focused on delirium prevention and recognition by bedside staff combined with computerized decision support facilitates safer prescribing of high‐risk medications and possibly results in less need for extended care.